ChemInform Abstract: Direct Construction of Fused Indoles by Gold‐Catalyzed Cascade Cyclization of Conjugated Diynes. Issue 33 (August 2015) - Naoe, Saori; Saito, Tatsuo; Uchiyama, Masanobu; Oishi, Shinya; Fujii, Nobutaka; Ohno, Hiroaki
Abstract A novel Gold‐catalyzed cyclization of conjugated diynes (I) bearing an ortho‐hydroxyethylamine substituent yields oxepino[1, 7‐a]indole derivatives (II) preferentially.